Physical Properties and Microbial Effect of Zinc Oxide NPs Rapid Biosynthesis by Microwave Irradiation - Amenah Isam Al-shammari; Zainab J. Shanan (Iraqi Journal of Physics)
This study used the green method to synthesise zinc oxide nanoparticles by microwave irradiation, using plant extracts of tea, coffee, and rosemary separately and Zn(NO₃)₂.6H₂O; this method is considered eco-friendly, rapid, and cost-effective. The structural properties of prepared materials were investigated with an X-ray diffractometer (XRD), atomic force microscope (AFM), Fourier transform infrared (FT-IR) spectroscope, and field emission scanning electron microscope (FE-SEM). Energy Dispersive X-ray (EDX) analysis was used to prove the presence of ZnO NPs. The electrical charge of the surface of nanomaterials was measured by Zeta potential, where 20 mV is adequate for ensuring physical stability. The three green extracts (tea, coffee, and rosemary) were 21.9, 14.7, and 15.5 mV, respectively. The shapes of the zinc oxide nanoparticles were irregular and agglomerated, and the average particle size was 59.96, 24.63, and 24.59 nm for the three extracts. Infrared spectroscopy using the Fourier transform (FT-IR) methods verified the presence of C=O, N-O, and C-H bonds; these results confirm the high reducing and capping capacity of ZnO NPs via biomolecules found in the plant extract. A UV-Vis spectrometer was used to study the light properties, and the energy gap was found to be 3.31, 3.26, and 3.35 eV for the tea, coffee, and rosemary extracts, respectively. Finally, ZnO NPs were used to inhibit the activity of many kinds of fungi and bacteria, both gram-positive and gram-negative. Studies have demonstrated their ability to penetrate the bacterial cell wall and halt the bacterial activity.